The Relationship Between Social Support and Postpartum Depression - Sayareh Hajipoor; Sedigheh Pakseresht; Maryam Niknami; Zahra Atrkar Roshan; Sima Nikandish (Journal of Holistic Nursing and Midwifery, 2021)
Introduction: Postpartum depression is a common and severe problem that has adverse effects on maternal and family health. Social support is one of the determinants of health, and in recent years has received increasing attention, and its overlook is a significant risk factor for postpartum depression. Objective: This study aimed to determine the relationship between social support and postpartum depression in women referring to comprehensive health centers in Rasht City, Iran. Materials and Methods: The present study is a cross-sectional, analytical study performed on 300 mothers referred to the comprehensive health service centers in Rasht 2-4 weeks after their deliveries. They were selected by cluster sampling method, which was done systematically within each cluster. The study data were collected using a three-part questionnaire of demographic characteristics, Edinburgh Postpartum Depression Scale (EPDS), and Hopkins social support. The obtained data were analyzed using descriptive and inferential statistics (t-test, Friedman, Mann-Whitney, Kruskal-Wallis, Spearman correlation coefficient, and rank logistic regression). Results: The results showed that the mean±SD age of the study mothers was 29±5.3 years. About 63.7% of mothers had low postpartum depression, and their mean±SD total score of social support was 64.03±16.92. The most support received from the spauses and parents. There was a statistically significant relationship between social support received by mothers after childbirth with education level (P=0.003), job (P=0.001), spauses’ job (P=0.001), income (P=0.001), residence status (P=0.043), number of deliveries (P=0.05) and pregnancy desire (P=0.047) and there was a significant inverse correlation between depression score and social support score by spauses (P=0.004, r=-0.167), parents (P=0.002, r=-0.176) and total social support score (P=0.024, r =-0.130). After adjusting for individual social variables, the effect of social support score on the part of the spauses (P=0.001), parents (P=0.006), friends, and relatives (P=0.033) continued to be associated with the severity of depression. Also, the number of deliveries (P=0.05) and h spauses’ jobs (self-employed) were significant compared to the unemployed ones (P=0.049). Conclusion: The results showed a significant and inverse relationship between social support and symptoms of postpartum depression. Although these results show the most support from spauses and parents, the amount of support received in the area of spauses’ ​​parents, friends, and relatives were low. It is necessary to draw the attention of midwives and health care providers to mothers and inform them about the importance of social support and its prominent role in reducing postpartum depression.